1999
DOI: 10.1067/msy.1999.95211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hospital volume on in-hospital mortality with pancreaticoduodenectomy

Abstract: Although volume-outcome relationships have been reported for many complex surgical procedures, hospital experience is particularly important with pancreaticoduodenectomy. Patients considering this procedure should be given the option of care at a high-volume referral center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
161
1
11

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(178 citation statements)
references
References 0 publications
5
161
1
11
Order By: Relevance
“…(30,34) The Institute of Medicine released its synthesis of the evidence that 77% of peer-reviewed studies found significant inverse relationships between hospital volume and mortality (34); and another systematic review by Dudley et al (30,34) reported similar findings. Extremely strong volume-outcome relationships have been chiefly identified for rare and high-risk procedures, including coronary artery bypass graft surgery, (35)(36)(37)(38)(39)(40) pediatric cardiac surgery,(41-43) unruptured abdominal aortic aneurysm repair, (39,44,45) total hip replacement, (30,34,46,47) and very high risk cancer surgeries such as for the pancreas, (48)(49)(50)(51)(52) esophagus, (50,53,54) and liver cancers. (53) …”
Section: Volume-outcome Relationships In High-risk Surgeriesmentioning
confidence: 99%
“…(30,34) The Institute of Medicine released its synthesis of the evidence that 77% of peer-reviewed studies found significant inverse relationships between hospital volume and mortality (34); and another systematic review by Dudley et al (30,34) reported similar findings. Extremely strong volume-outcome relationships have been chiefly identified for rare and high-risk procedures, including coronary artery bypass graft surgery, (35)(36)(37)(38)(39)(40) pediatric cardiac surgery,(41-43) unruptured abdominal aortic aneurysm repair, (39,44,45) total hip replacement, (30,34,46,47) and very high risk cancer surgeries such as for the pancreas, (48)(49)(50)(51)(52) esophagus, (50,53,54) and liver cancers. (53) …”
Section: Volume-outcome Relationships In High-risk Surgeriesmentioning
confidence: 99%
“…Past studies from the medical literature have found that both hospitals and surgeons that perform more Whipple surgeries in a given year have lower mortality rates (Birkmeyer et al, 1999;Ho et al, 2002). Many researchers believe that this volume-outcome relation reflects "practice makes perfect" or "learning by doing" (Luft et al, 1979;Sturm, 1999).…”
mentioning
confidence: 99%
“…This selective approach avoids the risks of operation in patients with benign lesions, but with current limitations in non-resectional diagnosis, cannot guarantee that a malignancy is not mistakenly being observed. Operative mortality rates following pancreatectomy range between 2 and 15 % and significant postoperative complications occur in approximately 45 % of patients [9]. Our data suggest that with current imaging and endoscopic techniques, a group of patients with pancreatic cysts can be identified with a malignancy rate of <3 % [8].…”
mentioning
confidence: 77%